2015
DOI: 10.1111/sjop.12216
|View full text |Cite
|
Sign up to set email alerts
|

Statements about true and false intentions: Using the Cognitive Interview to magnify the differences

Abstract: This study investigates the combined effect of the Cognitive Interview (CI) and the unanticipated questions approach on the magnitude of the elicited cues to true and false intentions. The participants (N = 125) planned for either a mock crime or a non-criminal event, half of them were interviewed with a standard interview (SI) and half with the CI. All participants were asked one set of questions targeting their intentions (anticipated questions) and one set of questions targeting the phase in which they plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
18
1
2
Order By: Relevance
“…Our core hypothesis was that truthful statements contained more detailed information than false statements and that this might be moderated by the instructions given to participants. The data did not support the hypothesis that truthful statements contain more detailed information than false statements which is in contrast to some previous intentions studies (Sooniste et al, 2015;Warmelink, Vrij, Mann, & Granhag, 2013, but see Sooniste et al, 2013). Those studies found that truthful statements tended to be richer in detail than false statements.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Our core hypothesis was that truthful statements contained more detailed information than false statements and that this might be moderated by the instructions given to participants. The data did not support the hypothesis that truthful statements contain more detailed information than false statements which is in contrast to some previous intentions studies (Sooniste et al, 2015;Warmelink, Vrij, Mann, & Granhag, 2013, but see Sooniste et al, 2013). Those studies found that truthful statements tended to be richer in detail than false statements.…”
Section: Discussioncontrasting
confidence: 56%
“…The authors found that truth tellers' answers were rated as more plausible than liars' answers but did not differ on the perceived amount of detail (for studies that do show such a difference in the richness of detail on intentions, see Sooniste et al, 2015;Warmelink et al, 2012;Warmelink, Vrij, Mann, Leal, et al, 2013). These findings were recently complemented with the Verifiability Approach (Jupe, Leal, Vrij, & Nahari, 2017).…”
Section: Detecting Deceptive Intentionsmentioning
confidence: 78%
See 2 more Smart Citations
“…In doing so, their lie contains many truthful aspects retrieved from previous experience. Although this is certainly ecologically valid, it is in stark contrast to experimental deception research where the lie is often a complete lie without resorting to previous experience (e.g., Sooniste, Granhag, Strömwall, & Vrij, 2015). The low proportion of passengers who did not make the trip before and the lack of that information from the original study do not allow us to further explore this explanation.…”
Section: Discussionmentioning
confidence: 90%